Should Overnight Orthokeratology Patients Wear Their Lenses During Their Afternoon Nap?. Issue 2 (February 2021) - Pérez-Corral, Joan; Cardona, Genis; Piñero, David P.; Aradilla, Yolanda; García, Mireia
Abstract : Purpose: The purpose of this study was to evaluate changes in visual acuity, corneal curvature, elevation, pachymetry, and objective quality of vision of experienced orthokeratology patients using their contact lenses during a simulated 30-min afternoon nap. Method: Twelve patients aged 30.8±8.3 years were recruited for the study, with a history of overnight orthokeratology of 27.4±23.0 months. Patients were instructed to close their eyes for 30 min while wearing their contact lenses or without lenses. Anterior corneal curvature, elevation, and corneal pachymetry were assessed with the Pentacam Scheimpflug System at 17 predefined corneal locations, and the HD Analyzer (Terrassa, Spain) was used to measure objective quality of vision. Measurements were conducted before eye closure (baseline), immediately after eye opening/lens removal (M1), and 30 min later (M2). Results: No statistically significant differences were found in anterior corneal curvature and elevation between baseline values and M1 or M2, with and without contact lenses. Corneal swelling at M1 was greater without contact lenses (change in central corneal thickness of 2.3%±3.1%, P =0.001) than with contact lenses (1.7%±1.3%, P <0.001). Recovery at M2 was slower when lenses were worn. A statistically significant improvement in objective quality of vision and visual acuity was found only when patients napped with their lenses. Conclusions: Even if no significant changes were found in corneal curvature and elevation, patients of overnight orthokeratology may benefit from using their contact lenses during their afternoon nap in terms of objective quality of vision and visual acuity.